Pengaruh Kualitas Layanan dan Kepercayaan terhadap Loyalitas Nasabah pada Koperasi Sepakat Jaya Rantauprapat - Nova Pradayanti; Midrawati Hasibuan; Sri Ayla (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the extent to which service quality and trust influence customer loyalty at Koperasi Sepakat Jaya Rantauprapat. The population of this research includes all registered members of the cooperative over the past year, totaling 696 individuals. From this population, 89 respondents were selected as the research sample. Data was collected using a Likert scale, and the study employed a descriptive quantitative approach with data analysis conducted through instrument testing, multiple linear regression, and classical assumption tests. The research findings revealed that two items in the instrument did not meet the validity criteria. The resulting regression equation was Y = 2.704 + 0.25X1 + 0.736X2 + e. Furthermore, the data showed a normal distribution, indicated by a significance value of 0.684, which is greater than 0.05. Hypothesis testing demonstrated that both service quality (X1), with a t-value of 4.439, and trust (X2), with a t-value of 14.569, exceeded the t-table value of 1.99. Therefore, H0 was rejected and H1 was accepted, indicating that service quality and trust significantly influence customer loyalty.